Approaching Integrated Hybrid Neural Circuits: Axon Guiding on Optically Active Semiconductor Microtube Arrays. Issue 24 (30th November 2016) - Koitmäe, Aune; Harberts, Jann; Loers, Gabriele; Müller, Manuel; Bausch, Cornelius S.; Sonnenberg, David; Heyn, Christian; Zierold, Robert; Hansen, Wolfgang; Blick, Robert H.
Abstract : Approaching integrated hybrid neural circuits : Axon guiding on optically active semiconductor microtube arrays. An array of optically active semiconductor microtubes is utilized to build highly defined neural networks enabling a remote optical detection of action potentials via changing electric field during propagation of action potentials. The axons in the tubes are detected via a confocal microscope.